Government Spending and Inclusive Growth in Developing Asia - Seok-Kyun Hur (Asian Development Bank (ADB), 2014)
This paper assesses the effects of fiscal policy on both equity and growth, specifically whether it is possible to design fiscal spending so that it enhances equity without sacrificing economic growth and vice versa. A cross-country panel vector autoregression (PVAR) using the World Development Indicators confirms the growth effects of individual fiscal spending items as anticipated whereas distributional effects were either temporarily positive or negligible for most fiscal items. However, compared with Organisation for Economic Co-operation and Development members, spending on public health and public education appeared to alleviate income inequality significantly in the Asian Development Bank members. This implies that fiscal expenditure policies may contribute more to inclusive growth in developing economies than in advanced ones.
hdl:11540/4211
Keywords: E62; H50; 330; Gini coefficient; government spending; inclusive growth; Panel Vector Autoregression; Gini-Koeffizient; Öffentliche Ausgaben; Wirtschaftswachstum; Verteilungsgerechtigkeit; Panel; VAR-Modell